Aroma analysis of rum prepared by rapid aging process - HAO Yadong, WANG Shiyu, CHEN Jinxiu, CUI Yang, LI Jingming (Zhongguo niangzao)
The rum was prepared by a rapid aging process, the composition of aroma substances was detected by headspace solid-phase microextraction (HS-SPME) combined with gas chromatography-mass spectrometry (GC-MS), and the changes in various aroma substances were analyzed in rum samples at different aging stages: pre-aging, initially-aging (golden rum), and post-aging (black rum). The differential flavor substances were screened by partial least squares discriminant analysis (PLS-DA), and the key aroma components were analyzed using odor activity value (OAV). The results revealed that a total of 55 volatile aroma substances were detected in the rapid aging rum, including 17 alcohols, 16 esters, 6 aldehydes, 5 ketones and 4 acids. The changes in these substances during the aging process conformed to the natural aging patterns. A total of 22 differential aroma substances were screened according to variable importance projection (VIP) value>1, including hexanal, isopentanol, octanoic acid, heptanal and 2-undecanone and so on, which were the key aroma substances affecting the rapid aging process. A total of 34 key aroma substances with OAV>1, of which 13 kinds of OAV>100. Combined with the sensory evaluation, the results showed that the rapid aging rum had an aroma style of typical sugarcane honey aroma, prominent fruity aroma and floral aromas. The aroma quality of the rapid aging rum met market demands, and its preparation process could be applied to rum production.